Food preservation, African style - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Bissap juice Bissap-based drinks made from Hibiscus sabdariffa, otherwise known as Guinea Sorrel, are popular in Senegal, where they are Produced as carbonated drinks on an industrial scale by the West African Brewery and by the private company...